mTOR, metabolism, and the immune response in HPV-positive head and neck squamous cell cancer - Joseph D. Coppock (KeAi Communications Co., Ltd., 2016)
Extensive preclinical studies have identified mammalian target of rapamycin (mTOR) activation as a frequent molecular signature underlying head and neck squamous cell carcinoma (HNSCC), including the distinct clinical subtype that is human papillomavirus (HPV) related, and have demonstrated the potential therapeutic utility of mTOR inhibitors in the treatment of these cancers. Numerous clinical studies have begun to evaluate this potential, however few have selected for and fewer have focused specifically on HPV-related disease. While HPV-positive (HPV+) HNSCC patients have a generally favorable prognosis, the overall number of patients who suffer failed treatment, recurrent disease, metastasis, and death is increasing due to the rapidly increasing incidence of HPV-related cancers. In this review, we discuss the rationale for proposing the adjuvant use of mTOR inhibition in the treatment of HPV+ HNSCC, highlighting the interplay of virally activated mTOR signaling, cellular metabolism, and the anti-tumor immune response. Keywords: Head and neck oropharyngeal carcinoma, Human papillomavirus, Metabolism, mTOR, Rapamycin